Ameliorative effect of supercritical fluid extract of Chrysanthemum indicum Linnén against D-galactose induced brain and liver injury in senescent mice via suppression of oxidative stress, inflammation and apoptosis. (24th April 2019) - Zhang, Xie; Wu, Jia-Zhen; Lin, Zhi-Xiu; Yuan, Qiu-Ju; Li, Yu-Cui; Liang, Jia-Li; Zhan, Janis Ya-Xian; Xie, You-Liang; Su, Zi-Ren; Liu, Yu-Hong
Abstract: Ethnopharmacological relevance: Chrysanthemum indicum Linne (C. indicum ), a healthy food and folk medicine in China for thousands of years, has been reported to exert heat-clearing and detoxifying effects and extensively applied to treat various symptoms such as inflammation diseases, hepatitis and headache. Aim of this study: The purpose of the present study was to investigate the protective effect of the supercritical carbon dioxide fluid extract from flowers and buds of C. indicum (CISCFE ) onD -galactose-induced brain and liver damage during aging process and to illuminate the underlying mechanisms. Materials and methods: Mice were orally administrated with CISCFE (100, 150 and 300 mg/kg) after injection withD -galactose. 24 h after the last administration, the blood samples, whole brain and liver tissues were collected for biochemical analysis, histological examination and western blot analysis. The body weight, spleen and thymus indexes, alanine transaminase (ALT), aspartate transaminase (AST), total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), malondialdehyde (MDA) in brain and liver, interleukin-1β (IL-1β), interleukin-6 (IL-6), and necrosis factor-α (TNF-α) were detected. Besides, the expressions of Bax, Bcl-2 and cleaved caspase-3 were determined by western blot assay. Results: The results indicated that CISCFE effectively increased the suppressed body weight, attenuated the decline of thymus and spleen indexes, and reduced the elevated levels of ALT and AST induced byD -gal. Furthermore, CISCFE might notably alleviateD -gal-induced abnormal alterations in structure and function of brain and liver dose-dependently via renewing normal antioxidant enzymes activities (SOD, CAT, GSH-Px), reducing MDA accumulation, decreasing inflammatory cytokines productions (IL-1β, IL-6, TNF-α), as well as attenuating the increase of Bax/Bcl-2 ratio and cleaved caspase-3 activation in the liver and brain. Conclusions: Taken together, our present results suggested that CISCFE treatment could effectively mitigate theD -gal-induced hepatic and cerebral injury, and the underlying mechanism might be tightly related to the decreased oxidative stress, inflammation and apoptosis, indicating CISCFE might be an alternative and promising agent for the treatment of aging and age-associated brain and liver diseases. Graphical abstract: fx1